On the Tacit Aspects of Science Pedagogy in Higher Education - Sitaraman, Ramakrishnan (Frontiers in Psychology, 2017)
In this article, we examine the concept of tacit knowledge and its implications for science education. We suggest that the history of scientific ideas and the personal nature of learning imply that higher education in scientific fields, wherein the generation of new knowledge, insights and understanding is paramount, would greatly benefit by acknowledging the irreducible role of the non-formal and the incidental in scientific innovation and advances.